The Mediating Effect of Self-Control on Depression and Tendencies of Eating Disorders in Adolescents - Li, Hong-Juan; Li, Jie; Qi, Meng; Song, Tian-He; Chen, Jing-Xu (Frontiers in Psychiatry, 2021)
Self-control is very important for the adaptation among adolescents. It is associated with depression and tendencies of eating disorders. This study aimed to investigate the relationship between the two and the mediating role of self-control for adolescents. In total, 1,231 adolescents (11–18 years) participated in this study. Self-control, depression, and tendencies of eating disorders were evaluated using the Dual-Mode of Self-Control Scale (DMSC-S), 11-item Kutcher Adolescent Depression Scale (KADS-11), and Eating Attitudes Test (EAT-26). The correlations among these factors were analyzed using mediating effect models. Girls had higher scores on the both subscales (impulse system and control system) of DMSC-S (P < 0.001). Those between 15–18 years had higher scores on impulse system than those between 11–14 years (P < 0.001). A significant mediating effect (12.8%) of the impulse system was observed between depression and tendencies of eating disorders in adolescents.